The Effect of Motivation, Competence and Work Environment on Employee Performance in Brawijaya Hospital Lawang Malang - Wardani, Silvia Intan; Peristiowati, Yuly; Nurwijayanti (Journal for Research in Public Health, 2020)
A hospital is a part of a health facility where the community obtains health services. One of the staff in the hospital who has a great influence on the quality of hospital services is the employee with his service. This study aims to determine the effect of motivation, competence and work environment on employee performance in Brawijaya Lawang-Malang Hospital. The sample in this study were all employees who worked as employees at Brawijya Lawang Malang Hospital as many as 102 people. The data analysis method used is linear regression. The results of the study show that motivation, competence and work environment together influence employee performance (n = 67,120; p = 0,000). While partially there is an influence between motivation on employee performance (n = 9.710; p = 0.023), between competency against employee performance (n = 5.894; p = 0,000), and between work environment on employee performance (n = 5.237; p = 0.000 ) Whereas the regression equation is Y = 1,721 + 0,518X1 + 1,072X2 + 0,137X3, where Y is performance, X1 is motivation, X2 is competence and X3 is work environment. While the value of Adjusted R Square 0.783 means that the variables of motivation, competence and work environment affect employee performance by 78.3% while the remaining 21.7% is influenced by other variables not included in this study. Management of Brawijya Lawang Malang Hospital needs to do tips to increase motivation, competence and pay attention to the work environment that can improve employee performance. Improving nurse performance can have an impact on improving the quality of hospital services